Resposta objetiva tumoral e taxas de sobrevida de pacientes com cirrose e carcinoma hepatocelular submetidos à radioembolização com ¹³¹I-lipiodol versus quimioembolização arterial - Ribeiro, Michele Costa de Oliveira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Introduction: Hepatocellular carcinoma (HCC) occurs mainly in the presence of cirrhosis and its treatment involves therapies such as transarterial chemoembolization (TACE), which is the most used nonsurgical therapy. However, the risk of complications associated with TACE is higher in cases of portal vein thrombosis (PVT), a finding that is not rare in HCC. Transarterial radioembolization (TARE) can be performed in the presence of PVT, but TARE with ¹³¹I-lipiodol was not sufficiently assessed in these cases. Objective: To compare the effectiveness of TACE and TARE with ¹³¹I-lipiodol regarding objective tumor reduction, measured through volumetric analysis of HCC images before and after the procedures. Methods: We evaluated 32 patients with HCC randomized to receive TACE or TARE with ¹³¹I-lipiodol. Locoregional response and survival rates were compared between the treatments. Results: 37 tumors were evaluated (19 received TACE and 18 received TARE with ¹³¹I-lipiodol, of which seven were associated with PVT). The median tumor reduction ranged from 37.6 to 47.3%, with no significant difference between the groups (p= 0.494) and regardless the PVT presence. The mean survival was 345 days, with no significant difference between groups (p= 0.656). However, mean survival in PVT cases was 196 days, which was lower than observed without PVT (p= 0.010). Conclusions: Both treatments promoted significant tumor reduction, showing that TARE with ¹³¹I-lipiodol is effective not only in cases without PVT, but also for those with this complication. These results suggest that TARE with ¹³¹I-lipiodol should be part of the HCC treatment, thus making locoregional therapy available for patients with PVT.

Introdução: O carcinoma hepatocelular (CHC) ocorre principalmente em portadores de cirrose e seu tratamento envolve terapias como a quimioembolização transarterial (TACE), que é a terapia não cirúrgica mais utilizada. Entretanto, o risco de complicações associadas à TACE é maior em casos de trombose de veia porta (TVP), que não é rara no CHC. A radioembolização transarterial (TARE) com ¹³¹I-lipiodol pode ser realizada na presença de TVP, mas não foi suficientemente avaliada nesses casos. Objetivo: Comparar a eficácia da TARE com ¹³¹I-lipiodol com a da TACE na redução tumoral, medida por meio da análise volumétrica de imagens do CHC antes e após os procedimentos. Métodos: Avaliamos 32 pacientes com CHC randomizados para receber TACE ou TARE com ¹³¹I-lipiodol. A resposta locorregional e as taxas de sobrevida foram comparados entre os tratamentos. Resultados: Foram avaliados 37 tumores (19 receberam TACE e 18 receberam TARE com ¹³¹I-lipiodol, dos quais sete estavam associados a TVP). A mediana da redução tumoral variou de 37,6% a 47,3%, sem diferença significativa entre os grupos (p=0,494) e independentemente da presença de TVP. A sobrevida média foi de 345 dias, sem diferença significativa entre os grupos (p=0,656). Entretanto, a sobrevida média nos casos de TVP foi de 196 dias, inferior à observada sem TVP (p=0,010). Conclusões: Ambos os tratamentos promoveram redução tumoral significativa, mostrando que a TARE com ¹³¹I-lipiodol é eficaz não apenas em casos sem TVP mas também para os que tenham essa complicação. Esses resultados sugerem que a TARE com ¹³¹I-lipiodol deve fazer parte do tratamento do CHC, tornando assim a terapia locorregional disponível também para pacientes com TVP.
Objective tumor response and survival rates patients with cirrhosis and hepatocellular carcinoma submitted to radioembolization with ¹³¹I-lipiodol versus arterial chemoembolization
Respuesta tumoral objetiva y tasas de supervivencia de pacientes con cirrosis y carcinoma hepatocelular sometidos a radioembolización con ¹³¹I-lipiodol versus quimioembolización arterial
Keywords: quimioembolização; quimioembolização terapêutica; radioembolização; radioembolização arterial; carcinoma hepatocelular; chemoembolization; therapeutic chemoembolization; radioembolization; arterial radioembolization; hepatocellular carcinoma